Tourist Intention to Visit Al-Jabbar Mosque using Theory of Planned Behavior (TPB) - Rayhan Syamsul Bahari; Fajar Sidiq Adi Prabowo (PT Mattawang Mediatama Solution, 2023)
The tourism sector is one of the potential sectors to be developed in Indonesia. The United Nations World Tourism Organization (UNWTO) predicts the number of tourists will reach 1.8 billion by 2030. West Java has great potential for the development of religious tourism in Indonesia. During the 2022 year-end holidays, 1.18 million tourists came to Bandung. To develop this potential, the local government inaugurated the Al Jabbar Mosque, Gedebage, Bandung City, West Java to become a new religious tourism destination in the West Java region as a center for Islamic education, religious tourism and a representative public interaction space for West Java and even ASEAN citizens. This study aims to validate tourists' observations of religious tourism in the city of Bandung, especially the Al Jabbar Mosque. The aspects to be studied include attitudes, subjective norms, and behavioral control, religiosity and knowledge of tourists in influencing the intention to visit and recommend religious tourism of the Al Jabbar Mosque. In realizing the objectives of this study, a quantitative research method is carried out, in the form of a survey, 15 question items will be made containing the theory of planned behavior. Questionnaire data will be processed using Partial Least Square Structural Equation Model (PLS-SEM) data analysis.